Employing graphics processing unit technology, alternating direction implicit method and domain decomposition to speed up the numerical diffusion solver for the biomedical engineering research - Jiang, Beini; Struthers, Allan; Sun, Zhe; Feng, Zhuo; Zhao, Xuqian; Zhao, Kaiyong; Dai, Weizhong; Zhou, Xiaobo; Berens, Michael E.; Zhang, Le (International journal for numerical methods in biomedical engineering, 2011)
Diffusion of biological compounds, including nutrients, oxygen, and chemoattractants, is a common component of biomedical engineering models. Conventional numerical schemes, such as alternating direction implicit (ADI) for diffusion, are frequently the computational bottleneck. Our study employs graphics processing unit (GPU) technology to accelerate the diffusion model simulation. We tailor, implement, analyze, and test several parallel ADI algorithms on the highly parallel computational and data architecture of the GPU. Our study confirms that the proposed algorithms provide fast, high‐quality simulation results suitable for inclusion in numerous bioengineering simulations. Copyright © 2011 John Wiley & Sons, Ltd.